2019
DOI: 10.1177/0363546519837935
|View full text |Cite
|
Sign up to set email alerts
|

Knee Pathology in Young Adults After Pediatric Anterior Cruciate Ligament Injury: A Prospective Case Series of 47 Patients With a Mean 9.5-Year Follow-up

Abstract: Background: The rate of secondary knee injuries after pediatric anterior cruciate ligament (ACL) injury is uncertain, and previous studies are limited because of poor methodology. Purpose: To evaluate the incidence of new meniscal injuries since the initial diagnostic magnetic resonance imaging (MRI) of young adults who sustained a pediatric ACL injury. In addition, to evaluate meniscal and cartilage injuries in the index knee and contralateral knee injuries on MRI at final follow-up (9.5 years). Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…At least 4143 (35%) patients were women; sex was not reported in 10 studies. Six studies included only patients who were skeletally immature as defined by remaining growth based on hand X-rays (n=3),52 57 70 open growth plates at X-rays and Tanner staging (n=2)53 71 or open growth plates at MRI (n=1) 72. Twenty-seven studies included only skeletally mature patients and 27 studies included a mixed population of patients aged under and over 16 years and did not clarify skeletal maturity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 4143 (35%) patients were women; sex was not reported in 10 studies. Six studies included only patients who were skeletally immature as defined by remaining growth based on hand X-rays (n=3),52 57 70 open growth plates at X-rays and Tanner staging (n=2)53 71 or open growth plates at MRI (n=1) 72. Twenty-seven studies included only skeletally mature patients and 27 studies included a mixed population of patients aged under and over 16 years and did not clarify skeletal maturity.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, there is no definitive evidence that other treatment strategies, such as non-operative treatment with optional delayed surgery, are superior to early surgery for reducing the risk of new meniscal tears. However, non-operative treatment with optional delayed surgery may be a reasonable alternative 14 24 72 88. An RCT can address some of the selection bias problems of non-randomised studies with regard to a question about treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that meniscal tears often heal spontaneously in that age group. 38 The clinically most relevant complaints relate to the distal and proximal patellar tendon Patellar tendinopathy is relatively common in adolescent athletes. In the literature, prevalence magnitudes of 5.8% (n=760, average age 13 years) and 7% (n=134, age 14-18 years) were reported for different sports.…”
Section: Discussionmentioning
confidence: 99%
“…21 Given these costs and the multitude of complications after ACL rupture including meniscal and cartilaginous damage, recurrent instability, and osteoarthritis, identification of predictive variables to identify those most at risk of ACL tears remains paramount. 8 10,18,28 Prior studies 5,12,29 have identified several extrinsic risk factors, including sport played, weather conditions, and landing patterns, that show some association with risk of ACL injury. Even more intrinsic risk factors have been identified, including sex, prior injury, ligamentous laxity, increased tibial slope, decreased notch width, and multiple genetic markers (ie, familial predisposition).…”
mentioning
confidence: 99%